Design and development of multiuse trolley - Khairul Azri, Ngadimen (2008)
Trolley is the main transport for human to carry load. Every trolley has different use and specific use. (It’s limited to do other job than the specification). There are some common problem can be detect at the trolleys nowadays such as don’t have stopper, load easy to fall (slips surface), heavyweight, only suitable for flat surface road, need many wheels, hard to cornering, not suitable for small area, cannot load many things, unstable for heavy duty work, high force needed to push or pull the trolley, hard to manufacturer and expensive material. To reduce this problem, one new trolley will be development that have multi function and has not limited to do another task or job. Nowadays, people use trolley to carry heavy load. There are many type of trolley in the market like industrial trolley, drum truck trolley and platform truck trolley. Many trolleys has been developed with a specific task or job like shopping trolley which can be use only for shopping, bagged trolley is only to carry bags, and transporting tray trolley only to carry trays. In the fabrication, there are many process involve to develop the product such as drilling, grinding, joining, measuring, gathering material, cutting material, and finishing process. This project is about design and fabricates a new product of trolley that has multi function. The trolley maximum loads must 200kg, multi use and easy assemble. Its also must reduce the disadvantages of the trolley in the current market like have stopper, adjustable and easy manufacturer. As the conclusion, this project had achieves its entire objective successfully. This project was done around thirteen week included almost all steps of the report such as literature review, design, fabrication process and others.